Pemodelan Poisson dan Binomial Negatif untuk Menganalisa Faktor Penyebab Angka Kejadian Abses Gusi - Neni Fikri Fauziah (Jurnal Keperawatan Silampari, 2022)
This research aims to analyze the comparison of Poisson and Binomial Negative modeling to the causative factors of gum abscess incidence in West Java. The research methods used are Poisson Regression and Binomial Negative. Predictors of this research are the habit of eating sweet foods (X1), the habit of consumption of sugary drinks (X2), the habit of never going to a dental medical personnel (X3). The results of the study obtained AIC values in negative binomial models smaller than in the Poisson regression model. In negative Binomial regression modeling, variables in the habit of eating sweet foods have a positive and significant effect on the incidence rate of Gingivitis in West Java with a value of CI 95%. Keywords: Regression, Binomial Negative, Poisson, Gum Abscess, Gingivitis